2020
DOI: 10.1021/acs.iecr.9b06092
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermodynamics and Experiment on Direct Synthesis of Dimethyl Carbonate from Carbon Dioxide and Methanol over Yttrium Oxide

Abstract: The thermodynamics on the direct synthesis of dimethyl carbonate (DMC) from CO2 and CH3OH was calculated and analyzed. Using Y­(NO3)3·6H2O as the precursor, a series of Y2O3 were prepared through the one-pot calcination method, which were employed to catalyze DMC synthesis. The decomposition temperature of Y­(NO3)3·6H2O was measured by thermogravimetric analysis, and Y2O3 was obtained after the precursor calcination at desired temperatures, denoted as Y2O3-T (°C). The catalysts were characterized by X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Other ZrO 2 -based catalysts have been studied ( Table 2, Entries 5-7) and the activity seems to be comparable to that in previous reports (Zhang et al, 2014;Li et al, 2017;Akune et al, 2018). It has been recently reported that Y 2 O 3 was an effective catalyst for the DMC synthesis from CO 2 and methanol ( Table 2, Entry 8), and it is characteristic that Y 2 O 3 has some activity at lower reaction temperature (363 K) than usual (for example, 383-423 K) (Sun et al, 2020). Unfortunately, the formation rate of DMC is not determined on Y 2 O 3 precisely, and the formation rate can be clearly higher than the estimated value.…”
Section: Oxide Catalystssupporting
confidence: 80%
“…Other ZrO 2 -based catalysts have been studied ( Table 2, Entries 5-7) and the activity seems to be comparable to that in previous reports (Zhang et al, 2014;Li et al, 2017;Akune et al, 2018). It has been recently reported that Y 2 O 3 was an effective catalyst for the DMC synthesis from CO 2 and methanol ( Table 2, Entry 8), and it is characteristic that Y 2 O 3 has some activity at lower reaction temperature (363 K) than usual (for example, 383-423 K) (Sun et al, 2020). Unfortunately, the formation rate of DMC is not determined on Y 2 O 3 precisely, and the formation rate can be clearly higher than the estimated value.…”
Section: Oxide Catalystssupporting
confidence: 80%
“…Current state of the art of DMC synthesis over ceria-based catalysts is detailed elsewhere [28]. Among rare earth oxide elements, Y 2 O 3 was also reported [29] to catalyze DMC synthesis at 353 K, one of the lower temperature reported for this reaction.…”
Section: Reactionmentioning
confidence: 99%
“…Wang and co-workers prepared a series of Y 2 O 3 -T catalysts through a one-pot calcination method from Y(NO 3 ) 3 •6H 2 O and applied them to study the thermodynamics of the direct synthesis of DMC from CO 2 . 171 The efficiency of DMC formation was closely related to the moderate acidity-basicity amounts of the catalysts. Y 2 O 3 -750 showed the best catalytic performance to give the highest yield of DMC at 90 °C under 8 MPa of CO 2 .…”
Section: Synthesis Of Dmc From Comentioning
confidence: 97%